AELITA BY YAKOV PROTAZANOV: MARS AS A COMPONENT OF THE UNCONSCIOUS OF THE 1920s’ INTELLECTUAL CHARACTER / «АЭЛИТА» ЯКОВА ПРОТАЗАНОВА: МАРС КАК ЧАСТЬ БЕССОЗНАТЕЛЬНОГО ГЕРОЯ-ИНТЕЛЛИГЕНТА 1920-х - SALNIKOVA EKATERINA V. / САЛЬНИКОВА Е.В. (Наука телевидения)
The article delves into Yakov Protazanov’s film Aelita (1924), marking its 100th anniversary. It aims to bring to light the nuances of the film, which were overlooked within Soviet film studies, while also highlighting the key differences between Alexei Tolstoy’s original novel and its cinematic adaptation. The Martian storyline, reimagined as the fantastical realm of engineer Mstislav Los by the screenwriters, can be interpreted as the subconscious of the intellectual hero of the 1920s in order to explore its symbolic meaning. The Martian landscape not only embodies governmental conservatism, but, through its constructivist style, symbolizes modernity, a technologically advanced civilization, as well as reflects concerns that come not from the past, but are projected towards the future. The paper analyzes the interplay between the fears and dreams of the intellectual protagonist, whose values were shaped before the 1917 revolution. Unlike his literary counterpart, the screen image of Los has changed: in the film, the engineer is an active man, an adventurer, a person of passion. The ethereal Aelita, the sovereign of Mars, is juxtaposed to Los’ wife, Natasha, a Soviet bureaucrat. While Natasha embodies the democratic ethos of an energetic Soviet woman, Aelita personifies aristocratic ideals. The emotional openness, energetic movements and tactile interactions, and active work and social contacts—the Soviet anthropological ideal—stand in contrast to the personal convictions of Los, who aestheticizes emotional restraint, interpersonal detachment, and social elitism. The article explores the motifs common to the Moscow and Martian storylines: the yearning for interplanetary connections, the need to transcend the usual mode of life in pursuit of something new, different, unattainable, and the willingness to make sacrifices for loftier objectives. In summary, the screenwriters have radically transformed the world of Tolstoy’s novel, which manifests the impotence of an individual in the face of revolutionary turmoil and emotional depression over the loss of a beloved one. Protazanov’s film underscores the importance of active participation of not only the Red Army soldier (Gusev), but also the intellectual (Los). While aligning with certain tenets of Soviet ideology, the film also contains subtexts that challenge it. Such is the (imaginary) revolution on Mars, which turns out to be driven not by a collective awakening among the working people of Mars, but rather by the individualistic ambitions of two Earthly men: the inertia of soldier Gusev’s ardor and the jealousy of intellectual Los, his detachment from with his Soviet wife and his yearning for emotional and erotic solace with a woman of royal lineage. The article surveys critical and theoretical analyses (both domestic and international) on Aelita, revealing motifs resonant with the Western European cinematic trends of the 1920s and of subsequent decades, from auteur (Robert Wiene, Fritz Lang, Andrei Tarkovsky) to popular science fiction films and series of the early 21st century (Cloud Atlas, Dune, Foundation, etc.). This reconfirms the scale of Protazanov’s Aelita, its predictive potential and artistic merit within the tapestry of global cinema. Статья посвящена фильму Якова Протазанова «Аэлита» (1924), отмечающему 100-летие создания. Ставится цель актуализировать и конкретизировать содержательные аспекты фильма, которые оставались в тени в советском киноведении. Поскольку марсианская линия превращена сценаристами в сон инженера Лося, она интерпретируется как бессознательное героя. Исследуется соотношение фобий и мечтаний интеллигента, чьи духовные ценности сформировались еще до революции 1917 года. Проводится сопоставление образов жены Лося, советской служащей Наташи, и воображаемой Аэлиты, правительницы Марса. Если Наташа воплощает демократические идеалы активной советской женщины, Аэлита является носительницей аристократических идеалов. Эмоциональная открытость и живая динамика, активность физических контактов, интенсивность общения и работы показаны в фильме как составляющие антропологического идеала советского человека. Этот идеал не совпадает с индивидуальными представлениями Лося, который в своем воображении эстетизирует эмоциональную сдержанность, межличностную дистанцию в повседневном пространстве, социальную элитарность технической интеллигенции. Рассматриваются смысловые оттенки мотивов, общих для московской и марсианской линий фильма: стремление к коммуникации с другими мирами, порыв к новому, другому, недосягаемому; необходимость в жертвовании своими достижениями или потребностями ради главных идеалов, целей жизнедеятельности. Наряду с содержательными аспектами, отвечающими советской идеологии, в фильме содержатся подтексты, этой идеологии противоречащие. Так, главным импульсом к (воображаемой) революции на Марсе фактически оказывается не рост самосознания марсианских трудящихся, а индивидуалистические устремления двух землян. Статья выявляет ряд мотивов, созвучных как западноевропейскому кинематографу 20-х годов, так и фильмам последующих десятилетий, как высокому авторскому кино (Фриц Ланг, Андрей Тарковский), так и популярным научно-фантастическим фильмам и сериалам начала XXI века («Облачный атлас», «Дюна», «Основание»). Это дополнительно подтверждает масштабность «Аэлиты» Протазанова, прогностический потенциал и художественную актуальность фильма в контексте мирового кинематографа.